Analysis of Disability Exclusion from Health care services of Bangladesh during Covid-19 (Social Science Review, 2026)
Disability is an emerging issue in public health services, however comparatively unrecognized population in terms of their accessibility. Bangladesh’s fragile public and highly commercial private health care service ensured their disparate community status more eloquent. Along with that, long-lasting traditional understanding also reinforces the circumstances, which set the spotlight on the deep crack in the COVID-19 pandemic-generated policy in Bangladesh. During the COVID-19, the Bangladesh government adopted policies, that ignored persons with disabilities (PWD) who experienced heightened vulnerability. Based on reviewing existing literature, policy papers, and documents this article tried to identify the country’s societal understanding of the community, psychosocial interpretation of existing medical interventions for them the rationing of emergency responses during COVID-19, and the failure of telemedicine services abruptly. Therefore, this article has significance because it presents the policy failure of the government and hints at adopting inclusive policies for the disabled population and setting significance for others.Social Science Review [The Dhaka University Studies, Part-D], Vol. 42, No.2, December 2025, pp. 23-38